(untitled) (Педагогіка вищої та середньої школи, 2009)
In the article the essence and contents of the notion of readiness of future teachers of foreign languages for personality-oriented teaching high-school pupils is revealed. On the basis of analysis of the literary sources the above mentioned phenomenon is defined and the ways of forming this complex unity of personality in students of the department of foreign languages are noted.